Research on fabrication of non-calcined geopolymer ceramics from kaolin Tung Ba, Vi Xuyen, Ha Giang - Lan, Tran Thi; Duong, Nguyen Anh; Anh, Phan Luu; Man, Tran Thi (Vietnam Journal of Earth Sciences, 2019)
The mineral component of kaolin clay in Tung Ba commune analyzed by X-ray diffraction is composed mainly of kaolinite (24–27%), illite (26–30%) and quartz (40–44%). Chemical composition (wt%) of Tung Ba kaolin determined by X-ray fluorescence (XRF) shows SiO2 at 59.92–64.98, Al2O3: 18.95–20.82, Fe2O3: 2.28–3.95, SO3: 2.47–4.66, CaO: 0.12–0.36, MgO: 1.72–2.13 and TiO2 at 0.75–1,08. To fabricate geopolymer ceramic, kaolin clay was transformed into metakaolin with the optimal parameters of calcination: the temperature at 750°C and heating time of 120 min. Obtained metakaolin is mixed with mixtures of NaOH/Na2SiO3 (40%wt) with ratios of 0.2, 0.25, 0.33, 0.5 and NaOH molarities are 10M, 12M, 14M. Testing geopolymer ceramics after 28 days had a compressive strength of 40–196 KG/cm2, water absorption of 15.25–17.98% and density of 1.54–1.69 g/cm3, totally satisfied the Vietnamese standard for construction bricks and ceramics.